Genome analysis for the identification of genes involved in phenanthrene biodegradation pathway in Stenotrophomonas indicatrix CPHE1. Phenanthrene mineralization in soils assisted by integrated approaches - Lara-Moreno, Alba; Merchán, Francisco; Morillo, Esmeralda; Zampolli, Jessica; Di Gennaro, Patrizia; Villaverde, Jaime (Frontiers in Bioengineering and Biotechnology, 2023)
Phenanthrene (PHE) is a highly toxic compound, widely present in soils. For this reason, it is essential to remove PHE from the environment. Stenotrophomonas indicatrix CPHE1 was isolated from an industrial soil contaminated by polycyclic aromatic hydrocarbons (PAHs) and was sequenced to identify the PHE degrading genes. Dioxygenase, monooxygenase, and dehydrogenase gene products annotated in S. indicatrix CPHE1 genome were clustered into different trees with reference proteins. Moreover, S. indicatrix CPHE1 whole-genome sequences were compared to genes of PAHs-degrading bacteria retrieved from databases and literature. On these basis, reverse transcriptase-polymerase chain reaction (RT-PCR) analysis pointed out that cysteine dioxygenase (cysDO), biphenyl-2,3-diol 1,2-dioxygenase (bphC), and aldolase hydratase (phdG) were expressed only in the presence of PHE. Therefore, different techniques have been designed to improve the PHE mineralization process in five PHE artificially contaminated soils (50 mg Kg-1), including biostimulation, adding a nutrient solution (NS), bioaugmentation, inoculating S. indicatrix CPHE1 which was selected for its PHE-degrading genes, and the use of 2-hydroxypropyl-β-cyclodextrin (HPBCD) as a bioavailability enhancer. High percentages of PHE mineralization were achieved for the studied soils. Depending on the soil, different treatments resulted to be successful; in the case of a clay loam soil, the best strategy was the inoculation of S. indicatrix CPHE1 and NS (59.9% mineralized after 120 d). In sandy soils (CR and R soils) the highest percentage of mineralization was achieved in presence of HPBCD and NS (87.3% and 61.3%, respectively). However, the combination of CPHE1 strain, HPBCD, and NS showed to be the most efficient strategy for sandy and sandy loam soils (LL and ALC soils showed 35% and 74.6%, respectively). The results indicated a high degree of correlation between gene expression and the rates of mineralization.